The Need to Address Social Adversities in Community Health - Ruhil, Rohini (Indian Journal of Community Health, 2016)
The paper is a perspective on the need to address social adversities in community health. Community Health today is restricted generally to clinical epidemiological studies and it is very important to research beyond ‘individual-level’ risk factors and ‘black-box’ epidemiology to a “multi-level eco-epidemiology. The material and social world around us plays a very important role in susceptibility or resistance to disease agents or risk factors. The focus here is on social phenomenon rather than on clinical manifestations of specific diseases or risk factors. The various social phenomenon discussed here include socio-economic status, education, income, poverty, employment, working conditions, job-strain, work-family conflict, social networks, social integration, social isolation, suicides, social security etc. It is recommended to intervene both at individual level as well as at larger structural level to influence government policies and society.